Growing out of the crisis: Hidden assets to Greece's transition to an innovation economy - Benedikt Herrmann; Alexander S. Kritikos (IZA Journal of European Labor Studies, 2013)
Greece's currently planned institutional reforms will help to get the country going with limited economic growth. With an economy based primarily on tourism, trade, and agriculture, Greece lacks an established competitive industry and an innovation-friendly environment, resulting in a low export ratio given the small size of the country and its long-time EU-membership. Instead, Greece exports only its nation's talent, with low returns. To become prosperous, the country must better capitalize on its Eurozone membership and add innovative sectors to its economic structure. Given Greece's hidden assets, such as the attractiveness of the country, a small number of strong research centers and an impressive diaspora in research, finance and business, we envision a Greek 'Silicon Valley' and propose a ten point policy plan to achieve that goal.
Keywords: L2; L26; O3; O4; 330; Innovation; Greece; Growth strategy; Entrepreneurship; Innovation systems; Regulatory environment